2018
DOI: 10.1186/s12889-018-5727-8
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of adolescent tobacco use and tobacco control policies in India

Abstract: BackgroundThis project will use a multilevel longitudinal cohort study design to assess whether changes in Community Tobacco Environmental (CTE) factors, measured as community compliance with tobacco control policies and community density of tobacco vendors and tobacco advertisements, are associated with adolescent tobacco use in urban India. India’s tobacco control policies regulate secondhand smoke exposure, access to tobacco products and exposure to tobacco marketing. Research data about the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…But frequent visits made by pregnant women for antenatal care could be opportunistically used for cessation advice. However, there is no provision for cessation services in antenatal clinics 26 .…”
Section: Discussionmentioning
confidence: 99%
“…But frequent visits made by pregnant women for antenatal care could be opportunistically used for cessation advice. However, there is no provision for cessation services in antenatal clinics 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Eastern region has a high disease and mortality from tobacco use. To address this burden, the impact of policy and domestic factors on the onset of youth tobacco use is necessary (Mistry et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 16 17 18 ] This could be due to the prevailing sociocultural practices in the region, wherein women never smoke as it is being considered a wrong and an unhealthy practice. [ 4 7 17 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco consumption has been linked with the development of variety of illnesses. [ 1 2 3 4 ] Even though, tobacco consumption has been quite common among men, the past few decades have witnessed a rapid surge among women as well. [ 5 6 7 ] The epidemiological analysis of various studies has revealed that women not only have a short latent period from the initiation of substance use to the onset or progression of the substance use disorders but are also even more susceptible to the adverse medical, psychiatric, and social consequences.…”
Section: Introductionmentioning
confidence: 99%